The PCAOB inspections process over global network firms: synthesizing the perspective of former inspectors with prior research - Maksymov, Eldar; Westermann, Kimberly D. (Review of Accounting Studies, 2026)
Calls for greater transparency in PCAOB inspections have intensified amid persistent concerns about opacity and inconsistency. We integrate prior academic research with in-depth interviews from 29 former PCAOB inspectors to construct a detailed, phase-based account of the inspection process over global network firms. We organize insights into four sequential phases—hiring, training, and performance assessment; planning; execution; and resolution—and present structured taxonomies that combine the literature with novel, practice-based observations. The paper’s primary contribution lies in organizing fragmented research and insider perspectives into a framework that clarifies how inspections operate in practice and where further research is critical. This synthesis provides a structured foundation for researchers, practitioners, and regulators seeking to evaluate and strengthen audit oversight—at a time when the structure and independence of the PCAOB itself faces renewed political scrutiny.